Effects of the Loess Plateau on Habitat Quality of the West Qinling Mountains, China - Caihong Hui; Xuelu Liu; Miaomiao Zhang; Xiaoning Zhang; Xingyu Liu (Ecology and Evolution)
ABSTRACT The West Qinling Mountains is the western extension of the Qinling Mountains, the geographic demarcation line between north and south China. Under the control of the Loess Plateau, the northern part of the West Qinling Mountains has obvious transitional features in terms of topography, climate, soil, and vegetation. In order to explore the effects of the Loess Plateau on habitat quality (HQ) of the West Qinling Mountains, we selected five typical counties with different percentages of the Loess Plateau area based on geomorphic types, climate, water system, vegetation zone, and elevation, and analyzed the spatial and temporal differentiation characteristics of HQ and their influence mechanisms with the help of the InVEST model and geographical detector (GD) model. The results showed that: (1) From 2000 to 2020, cultivated land continued to decrease, while constructed land continued to increase. The three regions showed a decreasing trend of cultivated land and an increasing trend of forest as the area of the Loess Plateau within the region decreases. The three counties in the Transition Zone showed a decreasing trend of the increase in forest and an increasing trend of the increase in construction land as the area of the Loess Plateau within the county decreases. (2) From 2000 to 2020, HQ changes showed a bipolar sharpening phenomenon. The three regions showed a decreasing trend in moderately low grade and an increasing trend in moderately high grade as the area of the Loess Plateau within the region decreases. The three counties in the Transition Zone showed an increasing trend of the increase in low grade and a decreasing trend of the increase in moderately high grade as the area of the Loess Plateau within the county decreases. (3) From 2000 to 2020, the mean HQ showed a trend of first increasing then decreasing. HQ of the Loess Plateau, the Transition Zone, and the West Qinling Mountains showed a three‐level gradient of low, medium, and high. The Transition Zone generally showed the spatial distribution characteristics of low in the north and high in the south, and the low grade was mainly distributed in the Loess Plateau area within the county north. The formation of this geographical distribution verified that the ecological environment of the Loess Plateau had influenced the HQ of the West Qinling Mountains. (4) Land use intensity (LUI) and population density were the dominant factors causing spatial differentiation of HQ in the three regions, NDVI and NPP have always played a key role in the variation of HQ in the Transition Zone, and the synergistic enhancement effect between various factors promotes the change of regional HQ.